The Influence of Social Media Marketing and Electronic Word of Mouth on Purchase Intention Through Brand Image (A Study on Eiger Product Consumers in Malang City) - Oktaviani, Fadhilah Nur; Sudarmiatin; Pratikto, Heri (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of social media marketing and electronic word of mouth on purchase intention through brand image among Eiger consumers in Malang City. The research aims to analyze the direct and indirect relationships among these variables. A quantitative explanatory approach was applied using SEM-PLS with 390 respondents. The results show that social media marketing and electronic word of mouth significantly affect brand image and purchase intention, while brand image also has a significant effect on purchase intention and mediates both relationships. These findings imply that firms should strengthen digital marketing and brand image strategies to increase consumer purchase intention.